Sexismo linguistico e nomes gerais: a construção de uma língua inclusiva - Marcos Paulo Santos (2019)
This study aims to analyze different ways of avoiding the use of masculine grammatical gender to denote both genders (men and women). The linguistic policy for an inclusive use of language have become more common in contemporary societies. As discussed by Bodelón and Rubio (2012), Bengoechea (2015), Mäder, Severo (2016) and Lagares (2018), these ideas are frequent targets of inquiries about relevance of prescriptive proposals that aim to avoid the linguisticsexism. The Rio Grande do Sul State developed a style guide for a non-sexist use of the language (TOLEDO et al., 2014). Through the variation and linguistic change, in Weinreich, Labov and Herzog (2006 [1968]), through the lexical variation, Biderman (2001), the notionsof linguistic norm (standard language) and prescription of uses, in Coseriu (1962, 1980) and Faraco and Zilles (2017), we pursued to observe the different linguistic forms to relate to men and women, especially regarding the use of general nouns. The general nouns are lexical items in grammaticalization processing. These names are very frequent in reference to human beings when the identification of specific characteristics such as sex is not requested or desired, they are endowed with low semantic features according to authors such as Halliday and Hasan (1995 [1976]), Amaral (2013a, 2013b), Amaral and Ramos (2014) and Mihatsch (2015). The data was prepared using AntConc software (ANTHONY, 2018). The search results allowed us toinvestigate 3680 occurrences in texts of speeches of parliamentarians in pronouncements of the legislative assemblies in Minas Gerais and Rio Grande do Sul States. The main results allowed us to classify the data regarding its use: sexist (2242 occurrences) and non-sexist (1438occurrences). There was a process of variation in the two States, but tended to a more marked change in Rio Grande do Sul State, where the non-sexist uses grew, accompanied by a drop of uses considered sexist. On the other hand, in the Minas Gerais State, the sexist uses increased.We observed that the uses of general nouns to outline human beings is a relevant strategy in the construction of an inclusive language. These names represented 26.7% of the total data, and 68.2% of the strategies considered non-sexist, with greater relevance of uses among theinformants of Minas Gerais State. Amongst the general nouns analyzed, pessoa(s) (person/people) was shown as a more frequent and relevant one as a non-sexist reference to humans, with 506 occurrences. The results also allow us to point out the possible existence in Rio Grande do Sul State of a greater concern with the use of a language with more equality between men and women by the existence of linguistic policies. It is possible to understand the effectiveness of different proposals for a non-sexist use of the language, as the uses of general nouns and other lexical strategies, as replicating nouns. These purposes have been frequent in the empirical use and best accepted by critics of the elaboration of an inclusive language.